2022
DOI: 10.7554/elife.79796
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potency of type VI amidase effector toxins is dependent on substrate topology and cellular context

Abstract: Members of the bacterial T6SS amidase effector (Tae) superfamily of toxins are delivered between competing bacteria to degrade cell wall peptidoglycan. Although Taes share a common substrate, they exhibit distinct antimicrobial potency across different competitor species. To investigate the molecular basis governing these differences, we quantitatively defined the functional determinants of Tae1 from Pseudomonas aeruginosa PAO1 using a combination of nuclear magnetic resonance (NMR) and a high-throughput in vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…To investigate, we used an orthogonal in vivo assay to directly test the effect of Tae1 activity in msbA-KD cells in the absence of Pae and other co-delivered H1-T6SS toxins. We measured lysis for rfp-KD and msbA-KD upon induction of exogenous wild-type Tae1 (Tae1 WT ) expression in the cell wall-containing periplasm 8,46 and found that msbA-KD had increased survival against Tae1 WT relative to rfp-KD ( Fig. 4a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate, we used an orthogonal in vivo assay to directly test the effect of Tae1 activity in msbA-KD cells in the absence of Pae and other co-delivered H1-T6SS toxins. We measured lysis for rfp-KD and msbA-KD upon induction of exogenous wild-type Tae1 (Tae1 WT ) expression in the cell wall-containing periplasm 8,46 and found that msbA-KD had increased survival against Tae1 WT relative to rfp-KD ( Fig. 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids for periplasmic Tae1 overexpression in Eco were constructed using splice-overlap extension cloning of tae1 WT and tae1 C30A coding sequences derived from P . aeruginosa (PAO1) into pBAD24 46,72 . A pelB leader sequence was fused to tae1 for localization to the periplasm.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the usual genomic environment of T6SS effector genes, we screened the MFE01 genome and identified a putative amidase of the Tae3 family, encoded downstream of an hcp gene in an hcp‐vgrG island, and located upstream of a gene of unknown function. Peptidoglycan‐targeting enzymes have been shown to be common T6SS effectors in pseudomonads, including the opportunistic pathogen P. aeruginosa (Chou et al, 2012; Radkov et al, 2022; Russell et al, 2011, 2012; T. Wang et al, 2020; Whitney et al, 2013). While MFE01 T6SS antibacterial activity and T6SS‐mediated potato protection are not abolished in a strain lacking Tae3, our results showed that Tae3 Pf contributes significantly to Pca and E. coli rounding and lysis.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate, we used an orthogonal in vivo assay to directly test the effect of Tae1 activity in msbA-KD cells in the absence of Pae and other co-delivered H1-T6SS toxins. We measured lysis for rfp-KD and msbA-KD upon induction of exogenous wild-type Tae1 (Tae1 WT ) expression in the cell wall-containing periplasm [8,48] and found that msbA-KD had increased survival against Tae1 WT Given the multigenic knockdown in msbA-lpxK-ycaQ in msbA-KD, these data suggest that msbA is a partial determinant of Tae1 susceptibility in the strain.…”
Section: Plos Pathogensmentioning
confidence: 94%
“…Plasmids for periplasmic Tae1 overexpression in Eco were constructed using splice-overlap extension cloning of tae1 WT and tae1 C30A coding sequences derived from P. aeruginosa (PAO1) into pBAD24 [48,81]. A pelB leader sequence was fused to tae1 for localization to the periplasm.…”
Section: Overexpression Plasmid Construction and Usementioning
confidence: 99%